A diagonal and social protection plus approach to meet the challenges of the COVID-19 syndemic: cash transfers and intimate partner violence interventions in Latin America. Issue 1 (January 2022) - Blofield, Merike; Knaul, Felicia M; Calderón-Anyosa, Renzo; Peterman, Amber; Franzoni, Juliana Martinez; O'Donnell, Megan; Bustreo, Flavia
Summary: Latin America has been particularly hard hit by the COVID-19 syndemic, including the associated economic fallout that has threatened the livelihoods of most families. Social protection platforms and policies should have a crucial role in safeguarding individual and family wellbeing; however, the response has been insufficient to address the scale of the crisis. In this Viewpoint, we focus on two policy challenges of the COVID-19 syndemic: rapidly and effectively providing financial support to the many families that lost livelihoods, and responding to and mitigating the increased risk of intimate partner violence (IPV). We argue that building programmatic linkages between social protection platforms, particularly cash transfers, and IPV prevention, mitigation, and response services, creates synergies that can promote freedom from both poverty and violence.